Scenario-based serious games repurposing - Protopsaltis, Aristidis; Auneau, Laurent; Dunwell, Ian; De Freitas, Sara; Petridis, Panagiotis; Arnab, Sylvester; Scarle, Simon; Hendrix, Maurice (SIGDOC'11 - Proceedings of the 29th ACM International Conference on Design of Communication, 2011)
Serious games are very content-rich forms of educational media, often combining high fidelity visual and audio content with diverse pedagogic approaches. This paper introduces scenario-based serious games repurposing and demonstrates repurposing a serious game into new learning objects. The process uses the scenario editor called "mEditor". Two case studies based on the Happy Night Club serious game are presented. The article describes exploratory work which continues the work that started within the mEducator project regarding repurposing serious games in order to enable their use and reuse in the same or different educational contexts. © 2011 ACM.
Created from Fastlane, Scopus look-up
Keywords: interactive learning environments; media in education; serious games; simulations; virtual reality